2007
DOI: 10.1523/jneurosci.1083-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Long-Term Memory by Exposure to Novelty Requires Protein Synthesis: Evidence for a Behavioral Tagging

Abstract: A behavioral analog of the synaptic tagging and capture process, a key property of synaptic plasticity, has been predicted recently. Here, we demonstrate that weak inhibitory avoidance training, which induces short-but not long-term memory (LTM), can be consolidated into LTM by an exploration to a novel, but not a familiar, environment occurring close in time to the training session. This memorypromoting effect caused by novelty depends on activation of dopamine D 1 /D 5 receptors and requires newly synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
437
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(482 citation statements)
references
References 39 publications
32
437
3
Order By: Relevance
“…Recently, several studies have shown that memories can interact with each other by means of synaptic tagging and capture (Almaguer-Melian et al, 2012;Ballarini et al, 2009;Moncada and Viola, 2007;Wang et al, 2010;Myskiw et al, 2013). All these studies show that exposure to novelty can upregulate the synthesis of PRPs, presumably through the release of dopamine, which are then captured at tagged synapses in a cooperative fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that memories can interact with each other by means of synaptic tagging and capture (Almaguer-Melian et al, 2012;Ballarini et al, 2009;Moncada and Viola, 2007;Wang et al, 2010;Myskiw et al, 2013). All these studies show that exposure to novelty can upregulate the synthesis of PRPs, presumably through the release of dopamine, which are then captured at tagged synapses in a cooperative fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Methylphenidate stimulates dopamine release in the forebrain by influences on the dopamine vesicular transporter (24)(25)(26)(27), and it was reported long ago to enhance learned behaviors in rats (28,29) and, more recently, in humans (30). The hippocampus detects novelty (31,32) and plays a key role in memory consolidation (2), which relies on novelty (33). Lisman and Grace (34) proposed that the detection of new information by the hippocampus is relayed to the ventral tegmental area (VTA) through the subiculum, accumbens, and ventral pallidum and that the VTA, in turn, projects to the hippocampus through dopaminergic fibers acting on D 1 receptors, where it enhances long-term potentiation (LTP) and learning.…”
Section: Discussionmentioning
confidence: 99%
“…Lisman and Grace (34) proposed that the detection of new information by the hippocampus is relayed to the ventral tegmental area (VTA) through the subiculum, accumbens, and ventral pallidum and that the VTA, in turn, projects to the hippocampus through dopaminergic fibers acting on D 1 receptors, where it enhances long-term potentiation (LTP) and learning. The hippocampal-VTA loop has, in fact, been found to be important for novelty detection (32), for the generation and maintenance of hippocampal LTP (35), and for memory consolidation (34,36). The VTA plays a key role in psychomotor stimulation, particularly in the generation of drug addiction, mediated by local glutamate receptors and dopamine projections to the accumbens and elsewhere (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Independent, but equivalent behavioral tagging experiments have been recently presented by Moncada and Viola using weak inhibitory avoidance (IA) training as tag and again open field exploration as the event triggering the burst of gene expression (Moncada and Viola, 2007). They found that a weak IA training, which induces short-but not long-term memory (LTM), could be consolidated into LTM by exploration to a novel environment occurring close in time, either before or immediately after, to the training session.…”
Section: Accepted Manuscriptmentioning
confidence: 99%